Association of Pro-Inflammatory Cytokines and Rubella Virus in Patients with Hashimoto’s Thyroiditis - A. I. K. Al-Kaif, Laith; K.H. Chabuk, Shahlaa; Rahman Hussein, Ali; Hasan R. Al-Zurfi, Ahmed; A. K. Al-Khafaji , Younis; Abd-Kadhum Al-Saadi , Mohammad; H. Al-Charrakh , Alaa; Ahmed Imran Al-Kaif , Rand (Hammurabi Journal of Medical Sciences, 2025)
Background: Hashimoto’s thyroiditis is an autoimmune disorder characterized by chronic lymphocytic infiltration of the thyroid and elevated proinflammatory cytokines. Environmental triggers, including viral infections, may contribute to disease pathogenesis. Objectives: This study evaluated the association of Rubella virus seropositivity, TNF-α levels, and body mass index with Hashimoto’s thyroiditis in an Iraqi population. Materials and Methods: A case-control study was conducted on 40 patients with Hashimoto’s thyroiditis and 40 healthy controls. Serum Rubella virus IgM was assessed using rapid test, TNF-α level was measured via enzyme linked immune sorbent assay and body mass index was calculated. Statistical comparisons were performed using Fisher’s exact and Welch’s t-test. Results: Females predominated in the Hashimoto’s thyroiditis group (92.5%) compared to controls (72.5%), though statistically significant (P = 0.037). Rubella IgM positivity was detected in 10% of Hashimoto’s thyroiditis patients and none of the controls (P = 0.116). Mean age (53.34 ± 11.39 vs. 42.95 ± 11.41 years), BMI (29.9 ± 3.27 vs. 21.5 ± 1.4 kg/m²), and TNF-α levels (60.42 ± 41.08 vs. 22.07 ± 7.32 pg/ml) were significantly higher in Hashimoto’s thyroiditis patients compared to controls (P ≤ 0.001). Conclusion: Hashimoto’s thyroiditis patient’s exhibit significantly higher BMI and TNF-α level compared to healthy controls, suggesting a pro-inflammatory and metabolic component in disease pathogenesis. Although Rubella IgM positivity was more frequent in patients, the difference was not statistically significant. Larger studies are needed to confirm viral contributions to Hashimoto’s thyroiditis.